2010
DOI: 10.1038/ng.666
|View full text |Cite|
|
Sign up to set email alerts
|

Common variants at 19p13 are associated with susceptibility to ovarian cancer

Abstract: Epithelial ovarian cancer (EOC) is the leading cause of death from gynecological malignancy in the developed world accounting for 4 percent of deaths from cancer in women1. We performed a three-phase genome-wide association study of EOC survival in 8,951 EOC cases with available survival time data, and a parallel association analysis of EOC susceptibility. Two SNPs at 19p13.11, rs8170 and rs2363956, showed evidence of association with survival (overall P=5×10−4 and 6×10−4), but did not replicate in phase 3. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
204
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(214 citation statements)
references
References 21 publications
4
204
2
Order By: Relevance
“…Molecular epidemiological studies have been conducted with the candidate gene approach to identify low penetrance susceptibility genes for ovarian cancer, many of which have showed inconsistent results [4][5][6][7][8][9][10][11] . Recent genome-wide association studies (GWASs) have reported 11 new singlenucleotide polymorphisms (SNPs) that are associated with ovarian cancer risk in European populations [12][13][14][15][16][17] . However, the results from the published GWASs have also demonstrated race-and ethnicity-specific cancer susceptibility 18 .…”
mentioning
confidence: 99%
“…Molecular epidemiological studies have been conducted with the candidate gene approach to identify low penetrance susceptibility genes for ovarian cancer, many of which have showed inconsistent results [4][5][6][7][8][9][10][11] . Recent genome-wide association studies (GWASs) have reported 11 new singlenucleotide polymorphisms (SNPs) that are associated with ovarian cancer risk in European populations [12][13][14][15][16][17] . However, the results from the published GWASs have also demonstrated race-and ethnicity-specific cancer susceptibility 18 .…”
mentioning
confidence: 99%
“…The present data should also encourage a molecular search for genes modifying survival, supported by recent evidence on such a locus at chromosome 19p13.11. 27 Serous histology was associated most strongly with the recently detected low-risk germline loci for ovarian cancer. 27,28 Transcriptome sequencing has recently revealed common somatic mutations in the ARID1A gene, encoding a subunit for the chromatin remodeling complex, in clear cell and endometrioid tumors, reinforcing the evidence that these types of ovarian cancers arise from endometriosis.…”
Section: Discussionmentioning
confidence: 91%
“…27 Serous histology was associated most strongly with the recently detected low-risk germline loci for ovarian cancer. 27,28 Transcriptome sequencing has recently revealed common somatic mutations in the ARID1A gene, encoding a subunit for the chromatin remodeling complex, in clear cell and endometrioid tumors, reinforcing the evidence that these types of ovarian cancers arise from endometriosis. 29 For incident discordant cancers, at least 2 independent associations were observed only for ovary-breast (3 independent associations) and ovary-prostate (2 associations).…”
Section: Discussionmentioning
confidence: 91%
“…Previously published genome-wide association studies (GWASs) also reported several single nucleotide polymorphisms (SNPs) that confer low-penetrance susceptibility to EOC [7][8][9]. Despite these successes in identifying genetic variations for ovarian cancer risk [10,11], no EOC GWAS data has been reported for Chinese women.…”
Section: Introductionmentioning
confidence: 99%